2007
DOI: 10.1007/s00248-007-9352-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Incubation Conditions on the Enrichment of Pyrene-degrading Bacteria Identified by Stable-isotope Probing in an Aged, PAH-contaminated Soil

Abstract: To determine whether the diversity of pyrene-degrading bacteria in an aged polycyclic aromatic hydrocarbon-contaminated soil is affected by the addition of inorganic nutrients or by slurrying the soil, various incubation conditions (all including phosphate buffer) were examined by mineralization studies and stable-isotope probing (SIP). The addition of nitrogen to either continuously mixed slurry or static field-wet soil incubations increased the rate and extent of mineralization of [(14)C]pyrene, with the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
40
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 47 publications
1
40
0
Order By: Relevance
“…SIP has been used to identify phylogenetically diverse bacteria capable of growth on PAHs ranging from 2 to 4 rings, including naphthalene ( Jeon et al, 2003;Singleton et al, 2005;Yu and Chu, 2005;Gutierrez et al, 2011;Jones et al, 2011a;Uhlik et al, 2012), anthracene ( Jones et al, 2011b;Zhang et al, 2011bZhang et al, , 2012, phenanthrene (Singleton et al, 2005(Singleton et al, , 2007Cébron et al, 2011;Jones et al, 2011a;Martin et al, 2012), pyrene (Singleton et al, 2006(Singleton et al, , 2007Jones et al, 2008;Jones et al, 2011a), fluoranthene ( Jones et al, 2011a), and benz [a]anthracene ( Jones et al, 2011a). A previous SIP study was conducted in this lab to identify aerobic anthracenedegrading bacteria in PAH-contaminated soil sampled from the site of a former manufactured gas plant ( Jones et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…SIP has been used to identify phylogenetically diverse bacteria capable of growth on PAHs ranging from 2 to 4 rings, including naphthalene ( Jeon et al, 2003;Singleton et al, 2005;Yu and Chu, 2005;Gutierrez et al, 2011;Jones et al, 2011a;Uhlik et al, 2012), anthracene ( Jones et al, 2011b;Zhang et al, 2011bZhang et al, , 2012, phenanthrene (Singleton et al, 2005(Singleton et al, , 2007Cébron et al, 2011;Jones et al, 2011a;Martin et al, 2012), pyrene (Singleton et al, 2006(Singleton et al, , 2007Jones et al, 2008;Jones et al, 2011a), fluoranthene ( Jones et al, 2011a), and benz [a]anthracene ( Jones et al, 2011a). A previous SIP study was conducted in this lab to identify aerobic anthracenedegrading bacteria in PAH-contaminated soil sampled from the site of a former manufactured gas plant ( Jones et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…Stable-isotope probing (SIP) is one cultivation-independent molecular technique that can link the identity of a microorganism with its metabolic function without isolating that organism from its natural environment (38). DNA-based SIP has been used to identify bacteria capable of degrading aromatic hydrocarbons in PAH-contaminated environments, and in some cases, it has revealed novel bacterial groups (15,16,33,35,43). Earlier SIP studies of pyrenedegrading bacteria conducted in our lab revealed members of previously uncultivated beta-and gammaproteobacterial groups, neither of which is related to any cultivated genus (16,35).…”
mentioning
confidence: 99%
“…DNA-based SIP has been used to identify bacteria capable of degrading aromatic hydrocarbons in PAH-contaminated environments, and in some cases, it has revealed novel bacterial groups (15,16,33,35,43). Earlier SIP studies of pyrenedegrading bacteria conducted in our lab revealed members of previously uncultivated beta-and gammaproteobacterial groups, neither of which is related to any cultivated genus (16,35). SIP investigations have also facilitated the isolation of ecologically relevant organisms (15,19,36) and have been used to reduce the complexity of community DNA slated for metagenomic analysis (4).…”
mentioning
confidence: 99%
“…One group, designated 'Pyrene Group 2' or 'PG2', had no cultivated relatives and could only be classified to the class Gammaproteobacteria. Subsequent SIP experiments using pyrene, benz[a]anthracene or fluoranthene [2,3] further implicated bacteria belonging to PG2 in the degradation of high-molecularweight PAHs as well as the low-molecular-weight PAH phenanthrene [4] and potentially the low-molecular-weight PAH anthracene [5]. The 16S rRNA gene sequences comprising PG2 from these SIP projects possessed a relatively high (!96 %) intragroup 16S rRNA gene identity.…”
mentioning
confidence: 99%
“…Strain TR3.2 T displayed growth on pyruvate as a carbon source with both nitrogen sources tested. Nitrate reduction was evaluated using the culture grown in sRB2 medium substituted with 5 mM KNO 3 . No nitrate reduction to nitrite beyond what was required for assimilation and growth was observed.…”
mentioning
confidence: 99%